Carbon mineralization potential and nutrient dynamics in soils under vegetation types and soil depths at Luot mountain - Thi Bich Phuong, Nguyen; Thi Bich Hoa, Nguyen; Thi Hang, Tran; Manh Hung, Bui; Pervez Khan (Journal of Forestry Science and Technology, 2024)
Soil mineralization is a crucial soil process that improves soil physical properties, enhances carbon sequestration, and provides essential minerals and available nutrients for plant growth. This study was conducted at five vegetation types and soil depths at Luot mountain area, located in VNUF campus, Hanoi city. Samples were incubated in the dark at 25°C and measured at intervals of 1, 2, 5, 10, 15, 25, 35, and 40 days in the laboratory to determine C-CO2 respiration from soils. The study showed that CO2 emissions were highest in topsoils and decreased with deeper soil depths. Mineralized C-CO2 decreased from Shrubs > Acacia + Native species (NS) > Pinus + NS > Native species > Control. CO2 emissions peaked early in the incubation period and then stabilized in the 40-day incubation period. Larger aggregates (≥ 5mm) decreased significantly under most vegetation types, except for Shrubs, where the reduction was minimal. Aggregate size ≥3mm increased post-incubation, notably under Pinus + NS and Native species, with smaller aggregates also increasing slightly. Organic matter content was highest in the topsoil but decreased post-incubation due to microbial C mineralization. There was an increase in soil organic matter at 10-20 cm and 20-40 cm layers after incubation, especially under Shrubs. Available nitrogen slightly increased in soils post-incubation for most vegetation types. Phosphorus content increased post-incubation, peaking under Shrubs, while potassium levels were generally poor but increased during incubation. The study found that C-CO2 mineralization was strongly associated with soil porosity and pH, suggesting that higher porosity and optimal pH enhance mineralization, with organic matter content being crucial for available nutrient cycles in soils.